Impact of Ethical Marketing Practices and Health Consciousness on Cosmetics Consumer Attitude and Purchase Intention: Evidence from Vietnam - Nguyen, Phuong Mai; Le, Huong-Linh; Ho, Nguyen-Nhu-Y; Dela Cruz, Rez Alexis; Tran, Luu Ly; Do, Vu Phuong Anh (International Review of Management and Marketing, 2024)
This study investigates the impact of ethical marketing practices and health consciousness on consumer attitudes and purchase intention for cosmetic products in Vietnam. A self-administered survey was conducted in August 2023 to collect data for our study. We received 250 valid responses after four months. SPSS software version 20 was employed for data analysis. Results showed that among three factors that affect consumer attitude, health consciousness played the most critical role, followed by product fairness and price fairness. Moreover, the attitude was confirmed in our study to affect the purchase intention of Vietnamese cosmetics consumers significantly. Our findings implied that cosmetic companies should tailor ethical marketing strategies to meet the preferences of Vietnamese consumers and boost their purchase intention.